Effects of silver nanoparticles (SNP) on Gerbera jamesonii cut flowers. (1st January 2011) - Solgi, Mousa; Kafi, Mohsen; Taghavi, Toktam Sadat; Naderi, Roohangiz; Eyre, Joseph X.; Joyce, Daryl C.
Gerbera vase life is most often terminated by stem bending and breaking or petal wilting. Effects of vase solutions containing 1 mg L –1 silver nanoparticles with or without 6% sucrose on gerbera 'deep purple' vase life, relative fresh weight, relative solution uptake, stem bending or breaking, stem end discolouration and ethylene production by petals, stem ends and stem necks were evaluated. The combination of SNP plus 6% sucrose increased vase life by 8 days compared with the deionised water control. Petal wilting and stem break were decreased by SNP plus 6% sucrose compared to the control. SNP plus 6% sucrose treatment enhanced ethylene production by petals, stem ends and stem necks during vase life. However, there were no obvious adverse effects of this increased ethylene on vase life parameters. Overall, results suggest that 1 mg L –1 SNP plus 6% sucrose has commercial potential as a vase solution for cut gerbera flowers.